1985
DOI: 10.1017/s0017089500006194
|View full text |Cite
|
Sign up to set email alerts
|

Sur la lacunarité des puissances de η

Abstract: La fonction η de Dedekind est définie paroù , Im(z)>0. C'est une forme modulaire parabolique de poids 1/2. Si r est un entier, la puissance r–ième de η s'écrit;où les coefficients pr(n) sone définis par l'identité.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 16 publications
0
78
0
1
Order By: Relevance
“…For lacunarity, the reader should consult [9], [24], [25] The case k = 12: the arithmetic density of their non-zero Fourier coefficients is 0) this theorem implies that 6lo(n)= i ~-6a4,x(4n + 5) almost always.…”
Section: Rll2( 8"c) = Q3inl~)i ( ] -Qsn)212mentioning
confidence: 99%
See 1 more Smart Citation
“…For lacunarity, the reader should consult [9], [24], [25] The case k = 12: the arithmetic density of their non-zero Fourier coefficients is 0) this theorem implies that 6lo(n)= i ~-6a4,x(4n + 5) almost always.…”
Section: Rll2( 8"c) = Q3inl~)i ( ] -Qsn)212mentioning
confidence: 99%
“…lo(4z) , = oUnfortunately, qS°dl°(q4) is not an Eisenstein series; it is a linear combination of an Eisenstein series and a cusp with complex multiplication[24].Let F(0 be the modular form with complex multiplication by Q(i) defined as F(r) = qa(r)r12(2z)q4(4z) = ~ a(n)q" = qx(n) = ~ z(d)d 4.a[nThe character ;~ is the same Dirichlet character mod 4 which occurred when k = 6. lo(4z) , = oUnfortunately, qS°dl°(q4) is not an Eisenstein series; it is a linear combination of an Eisenstein series and a cusp with complex multiplication[24].Let F(0 be the modular form with complex multiplication by Q(i) defined as F(r) = qa(r)r12(2z)q4(4z) = ~ a(n)q" = qx(n) = ~ z(d)d 4.a[nThe character ;~ is the same Dirichlet character mod 4 which occurred when k = 6.…”
mentioning
confidence: 99%
“…The coefficients are called D'Arcais numbers [Co74]. Independently from D'Arcais, Newman and Serre [Ne55,Se85] studied the polynomials in the context of modular forms. Serre proved a famous theorem on lacunary modular forms, utilizing the factorization of P n (x) for 1 ≤ n ≤ 10 over Q.…”
Section: Introductionmentioning
confidence: 99%
“…These coefficients were later considered by many authors, including Gupta, Atkin, Costello, Gordon, and finally Serre. Serre [16] showed that if r is an even integer, then {n : p r (n) = 0} has density zero if and only if r = 2, 4, 6, 8, 10, 14, or 26. Another natural question is about how large (as a function of r and n) the coefficients p r (n) are. In this regard, Newman's approach of expressing the coefficients p r (n) as polynomials in r is very ineffective.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%